Complete elimination of pest oxidation by high entropy refractory metallic silicide (Mo0.2W0.2Cr0.2Ta0.2Nb0.2)Si2. (December 2020) - Liu, Le; Zhang, Laiqi; Liu, Da
Abstract: Molybdenum disilicide (MoSi2 ) is a competitive ultra-high-temperature structural material. However, it suffered from a fatal low-temperature oxidation, which extremely limited its application. To solve this problem, a novel high entropy refractory metallic silicide with composition of (Mo0.2 W0.2 Cr0.2 Ta0.2 Nb0.2 )Si2 was synthesized by in-situ spark plasma reaction sintering in this work. The interrupted oxidation tests at 500 °C for 300 h have been performed, and shown that the prepared material has an excellent oxidation resistance at low temperatures without pest phenomenon. The mechanism for eliminating pest oxidation is that the high entropy of this material would suppress generation of bulk metallic oxides with formation of only an intact SiO2 film during oxidation. Graphical abstract: (a) The mechanism of (Mo0.2 W0.2 Cr0.2 Ta0.2 Nb0.2 )Si2 high-entropy silicide for eliminating pest oxidation is that the high entropy of this material would suppress generation of bulk metallic oxides with formation of only an intact SiO2 film during oxidation testing.(b) The formation process of the protective layer in reaction plane. (c, d) The differences in cationic atomic radius, as lead to lattice distortion and contribute to the sluggish diffusion effect. Image, graphical abstract